Study of protein extraction from residues of tambatinga amazon fish - Silva, Sumária Sousa e; Pettenon, Danieli Alini; Carvalho, José Wilson Pires; Guedes, Sumaya Ferreira; Loss, Raquel Aparecida (Ciência e Natura, 2022)
The present work aimed to extract proteins from tambatinga fish residue with physicochemical characterization, a hybrid of the crossing between the female tambaqui (Colossoma macropomum) and the male pirapitinga (Piaractus brachypomus). Protein extraction was performed by the following methods: acid (hydrochloric acid, acetic acid) and basic (sodium hydroxide). The protein fraction was characterized in relation to moisture content, ash, protein and yield. The moisture determination was performed with powder samples, submitted to drying at 40 ° C, in a forced circulation oven, which presented values of 7.29; 11.42 and 3.14% respectively. Regarding the fixed mineral residue (ash), the samples differed from each other, with values between 81.52; 50.65 and 44.76%. The samples obtained by the different processes presented protein contents of 3.63; 9.36 and 39.55% respectively. And the yield of protein extraction was 8.96; 3.64 and 6.43% for hydrochloric acid, acetic acid and sodium hydroxide, respectively. The obtained results indicate that it is possible to perform protein extraction for fish waste utilization, mainly by the basic extraction method.